Parents and teachers opinion about learning skills: Comparison between brazilian and italian dyslexic’s students - Capellini, Simone Aparecida [UNESP]; Giaconi, Catia; Germano, Giseli Donadon [UNESP] (My University, 2016)
The aim of this chapter is to describe and compare the response of parents and teachers of Brazilian and Italian Dyslexic’s students about learning skills. A total of 36 students with dyslexia were assessed by the Learning Skills Checklist (18 Brazilian dyslexic students and 18 Italians’s dyslexic students), from both genders, from 3rd to 5th grade of Elementary School. The Learning Skills Checklist included a total of six item, divided into attention skills, visual processing skills, hearing processing skills, mathlogical processecing skills, motor skills and behavioral skills. The teacher/parents should response in a scale from 0 to 3 points. The Learning Skills Checklist was distribuited to each parents and teacher students and the response was compared. In the comparison between the responses of teachers and parents of the Italian students, there was a significant difference in the visual processing skills, as teachers showed that the Italian dyslexic’s students had greater difficulties in visual processing when compared with the parent response. Regarding the same comparison in Brazilian population, there was no significant diferences in any skill. In comparison between the responses of parents between Brazilian and Italian population there was significant difference between attentional skills, visual processing skills, hearing processing skills, math-logical processing skills. Regarding Brazilian’s parents, their children had greater difficulties in these skills when compared to Italian parents. In comparison between the responses of teachers between Brazilian and Italian population, there were significant differences among attention skills, visual processing skills, math-logical processing and behavioral skills. Brazilian teachers indicated that their students had greater difficulties for those skills then Italian teachers, except for behavioral skill, which Italians teachers referred greater difficulties among theirs students. As a conclusion, parents and teachers of Italians students had different points of views of learning skills, indicating that Italian’s teachers are more perceptive of the student’s deficits. Regarding Brazilian population, there was no difference between parents and teachers response, indicating a lack of knowledge of dyslexics difficulties. However, when compared Italian and Brazilian population, was showed that teachers and parents of Brazilian’s students pointed out more difficulties in most of the skills, which can be assumed by the lack of public educational policy support for dyslexic students.
Keywords: Assessment; Checklist; Dyslexia